OPTIMALISASI PASOKAN BATUBARA UNTUK PEMBANGKIT LISTRIK DI KALIMANTAN TIMUR - Esterina Natalia Paindan; Nijusiho Manik (Sekolah Tinggi Teknologi MIGAS, 2019)
Population and economic growth cause demand for electricity in East Kalimantan is increasing. Therefore, energy readiness is needed to be able to meet the electricity needs. As an area that has abundant coal potential, therefore coal can be used as an alternative energy to replace petroleum and natural gas. Which the total capacity of the power plant in East Kalimantan until 2012 only 21.16% of them are using coal as their primary energy source. The purpose of this research is to optimize the supply of coal in obtaining the electric power supply mix based on primary energy source with the objective function of minimizing the total cost of electrical energy. The results of the linear programming simulation show that coal holds an important role in the supply of electricity to meet electricity needs in East Kalimantan which is 56%, while oil is 29%, natural gas is 13%, and hydropower by 2%.